Cicero's style : a synopsis, followed by selected analytic studies. - Albrecht, Michael Von. (Mnemosyne, Supplements, 2003)
This comprehensive study of Cicero's style discusses differences of literary genres (Ch.1), nuances of style within individual works (Ch.2), and chronological development (Ch.3), followed by an account of fixed elements typical of Cicero's diction (Ch.4). Finally, selected interpretative studies demonstrate the relationship of style and context in the orations, with special regard to literary form and political or moral content (Ch.5). The book concludes with an Epilogue on the De oratore and the culture of speech. Contrary to inveterate prejudices, Cicero does not confine himself to a single (so-called 'Ciceronian') style, but consciously and ably employs the full register of styles. The author points out in what respects a study of his style might be rewarding even today.